Dari trauma ke transendensi: Sebuah pendekatan teologis terhadap literasi kesehatan mental dalam kurikulum pendidikan Kristiani generasi digital - Jannes Eduard Sirait (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
The digital generation faces an unprecedented mental health crisis, with anxiety and depression rates rising dramatically since the 2010s. This article constructs a theological approach to mental health literacy as an integral component of a Christian education curriculum that is responsive to the needs of the digital generation. Through a constructive theological method with interdisciplinary analysis between trauma theology, developmental psychology, and transformative pedagogy, this study proposes a “from trauma to transcendence” framework that integrates theological understandings of suffering, grace, and healing with evidence-based mental health literacy principles. The result is a curriculum model that not only improves mental health literacy but also shapes resilient spirituality and hope rooted in the Christian narrative of healing and transformation. Abstrak Generasi digital menghadapi krisis kesehatan mental yang belum pernah terjadi sebelumnya, dengan tingkat kecemasan dan depresi yang meningkat drastis sejak dekade 2010-an. Artikel ini mengkonstruksi pendekatan teologis terhadap literasi kesehatan mental sebagai komponen integral kurikulum pendidikan Kristiani yang responsif terhadap kebutuhan generasi digital. Melalui metode teologi konstruktif dengan analisis interdisipliner antara teologi trauma, psikologi perkembangan, dan pedagogi transformatif. Penelitian ini mengusulkan kerangka